Fritz Reiner, maestro and martinet - Morgan, Kenneth, 1953- (Music in American life., 2005)
This award-winning book, now available in paperback, is the first solid appraisal of the legendary career of the eminent Hungarian-born conductor Fritz Reiner (1888-1963). Personally enigmatic and often described as difficult to work with, he was nevertheless renowned for the dynamic galvanization of the orchestras he led, a nearly unrivaled technical ability, and high professional standards. Reiner's influence in the United States began in the early 1920s and lasted until his death. Reiner was also deeply committed to serious music in American life, especially through the promotion of new scores. In Fritz Reiner, Maestro and Martinet, Kenneth Morgan paints a very real portrait of a man who was both his own worst enemy and one of the true titans of his profession.